2016
DOI: 10.1051/0004-6361/201525739
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and distribution of daughter species in the circumstellar envelopes of O-rich AGB stars

Abstract: Context. Thanks to the advent of Herschel and ALMA, new high-quality observations of molecules present in the circumstellar envelopes of asymptotic giant branch (AGB) stars are being reported that reveal large differences from the existing chemical models. New molecular data and more comprehensive models of the chemistry in circumstellar envelopes are now available. Aims. The aims are to determine and study the important formation and destruction pathways in the envelopes of O-rich AGB stars and to provide mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 92 publications
(114 reference statements)
8
46
0
Order By: Relevance
“…Gobrecht et al (2016) have modelled the inner wind region up to the dust formation zone and found SiO abundances that corresponded well with the observations of Decin et al (2010). Li et al (2016) have modelled the chemistry in the outer wind, using a gas-phas only chemical network. They assumed SiO to be one of the parent species, i.e.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Gobrecht et al (2016) have modelled the inner wind region up to the dust formation zone and found SiO abundances that corresponded well with the observations of Decin et al (2010). Li et al (2016) have modelled the chemistry in the outer wind, using a gas-phas only chemical network. They assumed SiO to be one of the parent species, i.e.…”
supporting
confidence: 57%
“…These profiles contain information on the ongoing circumstellar chemistry of a given molecular species, e.g. depletion of the species onto dust grains, and may be confronted with forward chemistry models that predict the abundance stratification of molecules throughout the stellar wind (see, e.g., Gobrecht et al 2016, Li et al 2016). Such models require certain stellar and dynamical parameters together with a set of parent species and their initial abundances as input, and solve a chemical network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, circumstellar chemical models have to 'inject' NH 3 at a high abundance (∼10 −6 -10 −5 ; as derived from observations) in the inner CSE (r < 10 16 cm) in order to explain the observed abundances of NH 3 and other nitrogenbearing molecules (e.g. Nercessian et al 1989;Willacy & Millar 1997;Gobrecht et al 2016;Li et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the CSE is smooth, nitrogen molecules at the inner radii may be shielded from dissociative photons by dust, H, H 2 , CO, and N 2 itself (Li et al 2013). Recent calculations by Li et al (2016) have shown that self-shielding of N 2 may shift its photodissociation region by about seven times further, to r∼10 17 cm in O-rich CSEs. The CO imaging survey by Castro-Carrizo et al (2010) has indicated a certain degree of clumpiness in AGB stellar winds.…”
Section: Introductionmentioning
confidence: 99%